Ligand-dependent development of the endothelial and hemopoietic lineages from embryonic mesodermal cells expressing vascular endothelial growth factor receptor 2 - Eichmann, Anne (The National Academy of Sciences of the USA, 1997)
The existence of a common precursor for endothelial and hemopoietic cells, termed the hemangioblast, has been postulated since the beginning of the century. Recently, deletion of the endothelial-specific vascular endothelial growth factor receptor 2 (VEGFR2) by gene targeting has shown that both endothelial and hemopoietic cells are absent in homozygous null mice. This observation suggested that VEGFR2 could be expressed by the hemangioblast and essential for its further differentiation along both lineages. However, it was not possible to exclude the hypothesis that hemopoietic failure was a secondary effect resulting from the absence of an endothelial cell microenvironment. To distinguish between these two hypotheses, we have produced a mAb directed against the extracellular domain of avian VEGFR2 and isolated VEGFR2+ cells from the mesoderm of chicken embryos at the gastrulation stage. We have found that in clonal cultures, a VEGFR2+ cell gives rise to either a hemopoietic or an endothelial cell colony. The developmental decision appears to be regulated by the binding of two different VEGFR2 ligands. Thus, endothelial differentiation requires VEGF, whereas hemopoietic differentiation occurs in the absence of VEGF and is significantly reduced by soluble VEGFR2, showing that this process could be mediated by a second, yet unidentified, VEGFR2 ligand. These observations thus suggest strongly that in the absence of the VEGFR2 gene product, the precursors of both hemopoietic and vascular endothelial lineages cannot survive. These cells therefore might be the initial targets of the VEGFR2 null mutation.